Congressional Responses to the Supreme Court's Constitutional and Statutory Decisions. (3rd April 2019) - Blackstone, Bethany; Goelzhauser, Greg
Abstract: We evaluate the frequency and form of legislative responses to Supreme Court decisions to evaluate the assumption that the legal basis of the Court's decision will determine the form of congressional response. Studies of Congress–Court interaction have often argued or assumed that Congress will respond to constitutional decisions with Court-curbing measures and to statutory decisions with policy-based measures, but recent scholarship suggests this distinction may be overstated. We introduce a new strategy for identifying policy-based responses and use new data to subject the conventional wisdom to empirical evaluation. In the period under consideration here (1997 to 2012), we find that the Court's statutory decisions appear to be nearly immune to Court-curbing attempts but are regularly targeted with policy-based responses, while a subset of constitutional cases (those that invalidate policies) are doubly vulnerable, triggering the introduction of Court-curbing bills and successful policy-based responses.